2011
DOI: 10.1037/a0021798
|View full text |Cite
|
Sign up to set email alerts
|

Stress buffering effects of daily spousal support on women's daily emotional and physical experiences in the context of breast cancer concerns.

Abstract: Daily spousal support appears to be an important contributor to the daily emotional and physical wellbeing of women with breast cancer. Contrary to the tenets of the stress buffering model, these data suggest that the buffering effect of spousal support is attenuated when breast cancer related emotional and physical concerns reach high levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 48 publications
(40 reference statements)
5
44
0
1
Order By: Relevance
“…All the above studies were small but corroborated each other's findings that a support person is key to providing guidance through the cancer journey. The need for support is not unique to sexual minority individuals and similar studies examining heterosexual couples corroborate these findings [31], but sexual minority individuals are more likely to be single [25].…”
Section: Emotional Supportsupporting
confidence: 65%
“…All the above studies were small but corroborated each other's findings that a support person is key to providing guidance through the cancer journey. The need for support is not unique to sexual minority individuals and similar studies examining heterosexual couples corroborate these findings [31], but sexual minority individuals are more likely to be single [25].…”
Section: Emotional Supportsupporting
confidence: 65%
“…Recent evidence from intensive longitudinal studies suggests that day-to-day fluctuations in support satisfaction can impact a range of health outcomes, including pain, fatigue, and mood [15,48,49]. In the present study, 40 % of the variability in satisfaction with spouse responses was within-person, and 60 % was between-person.…”
Section: Discussionmentioning
confidence: 60%
“…This is consistent with previous research among women with breast cancer which has shown that spousal support is associated with improved emotional and physical wellbeing and better quality of life [217].…”
Section: Social Support By Socio-demographic Characteristicssupporting
confidence: 82%
“…The provision of satisfactory emotional and informational support has been associated with better health and lower symptom intensity in women with breast cancer [212]. Both tangible support, in the form of a psycho-educational program, and affectionate support from family and friends, have been associated with better well-being and improved health-related quality of life (HRQOL) among breast cancer patients [213][214][215] While previous studies have reported that positive social support can enhance adjustment to breast cancer and improve HRQOL [215][216][217], these studies are largely cross-sectional. Little evidence has been presented that examines either the longitudinal impact of social support on HRQOL in women with breast cancer, or changes over time in social support and HRQOL throughout the course of the disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation